Sprint performance of elite wheelchair basketball players: Applicability of a laser system for describing the velocity curve - Ferro, A.; Villacieros, J.; Perez-Tejero, J. (Adapted Physical Activity Quarterly, 2016)
The purpose of this study was to develop a methodology to accurately analyze sprint performance of elite wheelchair basketball (WB) players in their own training context using a laser system and to analyze the velocity curve performed by the players regarding their functional classification and their playing position. Twelve WB players, from the Spanish men`s national team, took part in an oncourt 20-m-sprint test. BioLaserSport® was used to obtain time, mean velocities (Vm), maximum velocities (Vmax), and distances at 90%, 95%, and 98% of their Vmax. Vm and Vmax reached high values in Classes II and III and in the guard playing position. The protocol developed with the laser system makes it possible to obtain a precise velocity curve in short sprints and allows easy analysis of decisive kinematic performance variables in WB players, showing immediate feedback to coaches and players. The normalized data allow an interpretation of how much, where, and when Vmax occurs along the test.